Responsive predicates are question-embedding: Evidence from Estonian - Roberts, Tom (Proceedings of Sinn und Bedeutung, 2019)
The proper semantic treatment of the complements of Responsive Predicates (ResPs), those predicates which may embed either declarative or interrogative clauses, is a longstanding puzzle, given standard assumptions about complement selection. In order to avoid positing systematic polysemy for ResPs, typical treatments of ResP complements treat their arguments either as uniformly declarative-like (propositional) or interrogative-like (question). I shed new light on this question with novel data from Estonian, in which there are verbs think-like meanings with declarative complements and wonder-like meanings with interrogative complements. I argue that these verbs’ meaning is fundamentally incompatible with a proposition-taking semantics for ResPs, and therefore a question-taking semantics is to be preferred.